Effects of physiological integration on nitrogen use efficiency of moso bamboo in homogeneous and heterogeneous environments - Zhao, Jiancheng; Cai, Chunju (Frontiers in Plant Science, 2023)
Moso bamboo is one of the important clonal plants with complex underground rhizome-root system. Ramets connected by rhizome can translocate and share nitrogen (N), which may affect the nitrogen use efficiency (NUE) of moso bamboo. The aims of this study were to investigate the mechanisms of N physiological integration and its relationship with NUE of moso bamboo. A pot experiment was conducted to trace the movement of 15N between the connected ramets of moso bamboo in both homogeneous and heterogeneous N environments. Results showed that N translocation within clonal fragments of moso bamboo was detected in both homogeneous and heterogeneous environments. The intensity of physiological integration (IPI) was significantly lower in homogeneous environments than that in heterogeneous environments. 15N translocation between the connected ramtes of moso bamboo was determined by the source-sink relationship in heterogeneous environments, and the 15N allocation of the fertilized ramet was higher than that of the connected unfertilized ramet. The NUE of connected treatment was significantly higher than that of severed treatment, which suggested that physiological integration significantly improved the NUE of moso bamboo. In addition, the NUE of moso bamboo was significantly higher in heterogeneous environments than that in homogeneous environments. The contribution rate of physiological integration (CPI) on NUE in heterogeneous environments was significantly higher than that in homogenous environments. These results will provide theoretical basis for precision fertilization in moso bamboo forests.